Gonadotropin-Induced Spermatogenesis in CHH Patients with Cryptorchidism - Zhaoxiang Liu; Jiangfeng Mao; Hongli Xu; Xi Wang; Bingkun Huang; Junjie Zheng; Min Nie; Hongbing Zhang; Xueyan Wu (International Journal of Endocrinology)
Congenital hypogonadotropic hypogonadism (CHH) patients with cryptorchidism history usually have poor spermatogenesis outcome, while researches focusing on this population are rare. This study retrospectively evaluated gonadotropin-induced spermatogenesis outcome in CHH patients with cryptorchidism (n = 40). One hundred and eighty-three CHH patients without cryptorchidism were served as control. All patients received combined gonadotropins therapy (HCG and HMG) and were followed up for at least 6 months. The median follow-up period was 24 (15, 33) months (totally 960 person-months). Sperm (>0/ml) initially appeared in semen at a median of estimated 24 months (95% confidence interval (CI) 17.8–30.2). Twenty (20/40, 50%) patients succeeded in producing sperms, and the average time to produce first sperm was 19 ± 8 months. Five pregnancies were achieved in 9 (5/9, 56%) couples who desired for children. Compared with CHH patients without cryptorchidism (n = 183), cryptorchid patients had longer median time for sperm appearance in semen (24 months vs. 15 months, P<0.001), lower rate of spermatogenesis (50% vs. 67%, P=0.032), and lower mean sperm concentration (1.9 (0.5, 8.6) million/ml vs. 11.1(1.0, 25.0) million/ml, P=0.006) at the last visit. In conclusion, CHH patients with cryptorchidism require a longer period for gonadotropin-induced spermatogenesis. The successful rate and sperm concentration were lower than patients without cryptorchidism.